PERBERDAYAAN PEREMPUAN MELALUI PENGOLAHAN DAUN SINGKONG MENJADI PRODUK CAMILAN KHAS DESA PONDOK WULUH PROBOLINGGO - Farida Farida; Abdul Hafid Bahtiar; Ulil Hidayah (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Cassava is a type of tuber that is easy to grow and requires little maintenance. We found cassava plants in every area, especially in tropical areas and one of them was in the village of Pondok Wuluh Probolinggo. Cassava is a plant that has many benefits and is widely cultivated by the community. One of the benefits is that it can be processed into a variety of foods. Community empowerment in accordance with human dignity and as citizens. Empowerment as one of the central themes in community development is oriented in one direction and in line with the new paradigm. The production potential of cassava leaves in Pondok Wuluh Village can be used as cassava leaf chips in its production. This can be done by allocating resources to women who do not work by developing the processing of cassava leaves into chips. The implementation of this service uses information transfer and community development models, or an approach in which partners are directly involved in the implementation of community service as objects and subjects. Pondok Wuluh Village, Leces District, the cassava leaf carving program can be well organized and run smoothly according to the activity plan that has been prepared. This activity received a very good reception, as evidenced by the active participation of the training participants who did not leave the place until the end of the training. . The achievement of this activity is also with the formation of a group of entrepreneurs producing cassava leaves.